1991
DOI: 10.1007/bf01741346
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin-1 and tumour necrosis factor in non-Hodgkin's lymphoma patients

Abstract: Peripheral blood monocytes from non-Hodgkin's lymphoma (NHL) patients were assessed for the monocyte functions with respect to their ability to secrete interleukin-1 and tumour necrosis factor (TNF) and their cytotoxic potential to tumour target WEHI 164 clone 13. Our results indicate comparable levels of interleukin-1 and TNF production by NHL patients. The cytotoxic potential by monocytes was also not depressed in these patients. The data obtained suggest normal monocyte functions in NHL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The ability of monocytes to secrete these cytokines is a relevant assessment of their functional capacity. [23][24] The monocyte/macrophage function was studied with respect to their ability to produce IL-1, IL-6 and TNF in CLL patients, spontaneously and in presence of lipopolysaccheride, in comparison with normal population. Significantly decreased levels of IL The investigations presented here clearly indicate that the monocyte function is impaired and deficient in CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of monocytes to secrete these cytokines is a relevant assessment of their functional capacity. [23][24] The monocyte/macrophage function was studied with respect to their ability to produce IL-1, IL-6 and TNF in CLL patients, spontaneously and in presence of lipopolysaccheride, in comparison with normal population. Significantly decreased levels of IL The investigations presented here clearly indicate that the monocyte function is impaired and deficient in CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TNF elevated levels have also been found in the plasma of patients with various histological types of tumours (Balkwill et al, 1987), indicating that either various tumour cell types can produce this cytokine or that its production may rather reflect the immune response of the host against tumour. Others have reported that circulating TNF found in low-grade B-cell malignancies could be produced by peripheral blood monocytes (Adami et al, 1994;Jhaver et al, 1991). Interestingly, tumour-infiltrating lymphocytes obtained from lymphoma specimens have also been shown to preferentially secrete high levels of TNF upon autologous tumour cells stimulation (Schwartzentruber et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the purine analogs on the treatment schedules of LG-NHL (11)(12)(13)(14)(15)(16) the number of biological studies of these slow proliferative activity diseases is growing. Tumor necrosis factor alpha (TNF-a) and soluble CD23 (sCD23) (the CD23 antigen is a 45-kd transmembrane glycoprotein that binds immunoglobulin E with low affinity; the spontaneous proteolytic cleavage of CD23 results in the generation of soluble fragments) concentrations have been reported to significantly predict treatment outcome of disease in B-cell chronic lymphocytic leukemia and in a few patients with LG-NHL (17)(18)(19)(20).…”
Section: Itroductionmentioning
confidence: 99%